The Impact of the Decision of the Constitutional Court Number 30 / PUU-XVI / 2018 on the Institution of the Regional Representative Council - Muhammad Al-Fatih; Mujar Ibnu Syarif; Abdul Qodir (STAATSRECHT: Indonesian Constitutional Law Journal, 2021)
This study aims to determine the background of the filing of the Constitutional Court case lawsuit Number 30 / PUU-XVI / 2018 and understand the influence of the Constitutional Court decision Number 30 / PUU-XVI / 2018 on the Institutional Council of Regional Representatives. The research method used in this research is juridical normative with a statutory approach, a historical approach, and a conceptual approach obtained from data collection techniques through literature study through the statutory regulatory approach that refers to the 1945 Constitution, the Law, and the Constitutional Court Decisions. related to the theme of the discussion. The results of the study show that the background for filing a lawsuit against the Constitutional Court Decision Number 30 / PUU-XVI / 2018 is that there is no clear meaning to the phrase “other work” in Article 182 letter I of the Election Law that has provided space for political party functionaries as candidate members DPD. In addition to the impact of the decision of the Constitutional Court Number 30 / PUU-XVI / 2018 is the issuance of the Final List of Candidates (DCT) for DPD candidates issued by the General Elections Commission (KPU) as a follow-up to implementing the Constitutional Court Decision in which the KPU has crossed out the candidates. DPD members who still serve as functionaries of political parties.